Paediatric hospitalisations for lower respiratory tract infections in Mount Isa. Issue 10 (2nd June 2014) - Janu, Elisabeth K; Annabattula, Bhavana I; Kumariah, Saampavi; Zajaczkowska, Marta; Whitehall, John S; Edwards, Matthew J; Lujic, Sanja; Masters, Ian B
Abstract: Objective: To compare the rates of acute lower respiratory tract infection (ALRI) among children in north‐west Queensland, according to age, sex and Indigenous status. Design, setting and patients : Retrospective chart review of hospitalisations at Mt Isa Base Hospital, Queensland, from 1 January 2007 to 31 December 2011 among children < 15 years of age. Main outcome measures: Rates of admission for bronchiolitis, pneumonia and bronchiectasis, calculated using population data from the Australian Bureau of Statistics. Results: There were 356 admissions for ALRI, involving 276 children. Of the 162 children aged < 12 months old, 125 (77.2%) were Indigenous. Hospitalisations increased over the study period, and rates were significantly higher among Indigenous children compared with non‐indigenous children (24.1 v 4.5 per 1000 population per year). There were 195 admissions of 164 children with pneumonia, 126 (76.8%) of whom were Indigenous. Annual rates for Indigenous children were higher than for non‐Indigenous children (13.7 v 2.3 per 1000 population). Multiple admissions were common. One‐third presented with gastrointestinal symptoms and signs. Pneumococcal disease persisted despite vaccination. There were 160 hospitalisations for bronchiolitis; 114 occasions (71.3%) involved Indigenous children. Seven children had bronchiectasis; all were Indigenous. Conclusion: Rates of ALRI in Mt Isa are comparable to those in the Northern Territory, which is reported to have rates of pneumonia among the highest in the world for children < 12 months of age. Multiple admissions are common, suggesting an even higher rate of bronchiectasis. Pneumonia may present as gastrointestinal disease, and invasive pneumococcal infection must be suspected despite vaccination.